2011
DOI: 10.1103/physreva.84.043619
|View full text |Cite
|
Sign up to set email alerts
|

Confinement-induced resonances in anharmonic waveguides

Abstract: We develop the theory of anharmonic confinement-induced resonances (ACIR). These are caused by anharmonic excitation of the transverse motion of the center of mass (COM) of two bound atoms in a waveguide. As the transverse confinement becomes anisotropic, we find that the COM resonant solutions split for a quasi-1D system, in agreement with recent experiments. This is not found in harmonic confinement theories. A new resonance appears for repulsive couplings (a3D > 0) for a quasi-2D system, which is also not s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…Recent experimental advances allowed to explore the corresponding physics of CIRs in quasi-one-and quasi-two-dimensional (quasi-1D and quasi-2D) waveguide geometries [11][12][13][14][15] or in mixed dimensional scattering processes [16]. Complementing the experimental studies, substantial theoretical efforts exhibit a kaleidoscope of confinement-induced processes, such as dual [17] and higher partial wave CIRs [18,19], multichannel [20][21][22][23] or anharmonic CIRs [24][25][26] and CIR molecule formation [27] or dipolar CIRs [28][29][30]. Further studies on CIR effects focus on the impact of various confining geometries, such as quasi-2D either harmonic [31,32] or square well [33], and lattice potentials [34][35][36], or collisions in mixed dimensions [37].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental advances allowed to explore the corresponding physics of CIRs in quasi-one-and quasi-two-dimensional (quasi-1D and quasi-2D) waveguide geometries [11][12][13][14][15] or in mixed dimensional scattering processes [16]. Complementing the experimental studies, substantial theoretical efforts exhibit a kaleidoscope of confinement-induced processes, such as dual [17] and higher partial wave CIRs [18,19], multichannel [20][21][22][23] or anharmonic CIRs [24][25][26] and CIR molecule formation [27] or dipolar CIRs [28][29][30]. Further studies on CIR effects focus on the impact of various confining geometries, such as quasi-2D either harmonic [31,32] or square well [33], and lattice potentials [34][35][36], or collisions in mixed dimensions [37].…”
Section: Introductionmentioning
confidence: 99%
“…coupling can have a significant impact on an ultracold atomic quantum gas. In [5,6] it was revealed that the particle loss and heating observed in [7] was caused by inelastic confinement-induced resonances (CIR), i. e. resonances due to the c.m.-rel. coupling of a c.m.…”
Section: Introductionmentioning
confidence: 99%
“…For β = 0.427471, this models an actual atom-trap interaction [1,11,12] in modern experiments [13] on ultracold atoms (figure 1). The atom-atom interaction is taken of Gaussian form:…”
Section: Resultsmentioning
confidence: 99%